PEMODELAN KETAHANAN HIDUP PASIEN PENDERITA HIV DENGAN REGRESI COX PROPORTIONAL HAZARD - Resti S, Siska; Rosita, Silvia (AKTUARIA, 2022)
The purpose of this study was to model the survival time of HIV patients using cox proportional hazard regression and find out the factors that significantly affect the survival time of ODHA undergoing ART to entering the AIDS stage. The study population was all HIV patients at the Dharmais Cancer Hospital, Jakarta. The research sample based on purposive sampling technique was HIV patients on antiretroviral therapy. The results showed that the factors that affected the survival time of patients undergoing antiretroviral therapy until they entered the AIDS stage were initial CD4 status, clinical stage, mode of transmission, gender, education, age and working status. Patients infected with HIV through injecting needles (drug users), did not finish junior high school (graduated elementary school or did not attend school) and were working when starting ART have the highest risk of failure (hazard) compared to other categories